Optimum dosage of 5-aminosalicylic acid as rectal enemas in patients with active ulcerative colitis. Issue 8 (August 1991) - Campieri, M; Gionchetti, P; Belluzzi, A; Brignola, C; Tampieri, M; Iannone, P; Miglioli, M; Barbara, L
Abstract : 5-Aminosalicylic acid (5-ASA), the active moiety of sulphasalazine (SASP), was given as a rectal enema to patients with mild to moderate distal ulcerative colitis to determine the minimum effective dosage. A double blind study was carried out using enemas containing 1, 2, or 4 g or 5-ASA or placebo for a one month treatment period. One hundred and thirteen patients with ulcerative colitis attending our outpatient clinic volunteered to participate. Clinical, sigmoidoscopic, and histological assessments were carried out at the beginning of the study and after 15 and 30 days of treatment. All patients who received 5-ASA enemas showed significantly better results than those who received a placebo enema (p less than 0.001) but no difference was detected among the patients receiving differing concentrations of 5-ASA. This study suggests that 1 g 5-ASA (in a 100 ml enema) is a sufficient dosage for patients with a mild to moderate attack of ulcerative colitis.